Perinephric pseudocyst in a cat: management by ultrasound-guided drainage - ADAMAMA-MORAITOU, K. K.; PARDALI, D.; VAFIADIS, I.; PATSIKAS, M. N.; PRASSINOS, N. N. (Journal of the Hellenic Veterinary Medical Society, 2018)
A 15-year-old castrated DSH cat was presented with a sudden onset of abdominal distension of 10 days duration. Polyuria/polydipsia, sporadic vomiting and weight loss were also mentioned by the owners. Distension of the cranial abdomen was observed on admission, and two smooth masses were palpated in the abdomen. Mild anemia and azotemia were detected on hematological and biochemical testing. Plain lateral and dorsoventral radiographic views of the abdomen were compatible with renomegaly. Ultrasonography revealed the presence of fluid surrounding both kidneys, and analysis of the accumulated fluid confirmed the diagnosis of bilateral subcapsular transudative perinephric (perirenal) pseudocysts. The precise etiology of pseudocysts formation in our cat could not be identified. Emphasis is placed on their development, due to the coexisting chronic kidney disease, but also to other causes. Although surgical or laparoscopical resection of the cyst wall is generally recommended, owners of this cat elected periodical ultrasound-guided drainage of the perinephric fluid. This might be a reasonable decision, due to its advanced age and the macroconcurrent moderate chronic kidney disease. The long term outcome was favorable, with permanent remission of the perinephric pseudocysts after only three evacuations. The cat died, approximately 20 months after the initial presentation, due to deterioration of chronic kidney disease, and perinephric pseudocysts could not be detected clinically at that time.